2013
DOI: 10.1590/0037-8682-1506-2013
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant factors, nitric oxide levels, and cellular damage in leprosy patients

Abstract: Introduction:The immune response caused by Mycobacterium leprae is a risk factor for the development of oxidative stress (OS) in leprosy patients. This study aimed to assess OS in leprosy patients before the use of a multidrug therapy. Methods: We evaluated the nitric oxide (NO) concentration; antioxidant capacity; levels of malondialdehyde, methemoglobin and reduced glutathione; and the activity of catalase and superoxide dismutase (SOD) in leprosy patients. Results: We observed lower SOD activity in these le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
(14 reference statements)
3
12
0
Order By: Relevance
“…However, there was no difference between MDT-treated and untreated patients (Figure 2a). These data showed that the disease process appears to be responsible for the detected NO increase in the body, as shown by our previous report [43] and other studies [44], [45].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…However, there was no difference between MDT-treated and untreated patients (Figure 2a). These data showed that the disease process appears to be responsible for the detected NO increase in the body, as shown by our previous report [43] and other studies [44], [45].…”
Section: Resultssupporting
confidence: 88%
“…These data were similar to other studies that reported that untreated leprosy patients have decreased levels of SOD compared to healthy individuals [51], and that even after the use of MDT, the SOD levels remained low. These findings indicate that oxidative stress related to the reduction of antioxidants and free radical increase observed in these patients may also be caused by Mycobacterium leprae , as reported in a previous study [43], [51]. Furthermore, studies reported that reduction of CAT activity may be associated with factors related to individuals, such as enzymatic deficiencies due to genetic mutations or a reduced synthesis of this enzyme by changes in their gene expression [52].…”
Section: Resultssupporting
confidence: 73%
“…Considering the aspects observed during the course of this chapter, macrophages have a crucial role in inducing the immune response to M. leprae, and their uptake capacity, phagocytosis, and microbicidal activity may depend on the microenvironment. Macrophages, after the interacting with either the bacilli or its wall components, are able to induce oxidative stress [10][11][12][13][14] and to induce various receptors as scavenger receptors [6,16,23,24,34,[42][43][44] and PRR [53][54][55]69], leading to the polarization of their response. In an anti-inflammatory profile (M2), this cell induces increased uptake of lipids [21,22] and Hb-haptoglobin [16,42], which aid the growth of M. leprae by the activation of the enzymes IDO [42,45], HO-1 [42] and arginase [37].…”
Section: Resultsmentioning
confidence: 99%
“…2 production of nitric oxide, thus causing peripheral nerve damage characteristic of patients with leprosy [10]. Other studies have shown the ability of M. leprae to induce the production of oxidative mediators and their products, peroxynitrite and nitrotyrosine [11][12][13][14].…”
mentioning
confidence: 99%
See 1 more Smart Citation